2020
DOI: 10.3390/pathogens9060435
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Tests for Onchocerca volvulus in the Democratic Republic of Congo

Abstract: Onchocerciasis is diagnosed by detecting microfilariae in skin snips or by detecting OV16 IgG4 antibodies in blood by either enzyme linked immunosorbent assay (ELISA) or a rapid diagnostic test (RDT). Here, we compare the sensitivity and specificity of these three tests in persons with epilepsy living in an onchocerciasis endemic region in the Democratic Republic of Congo. Skin snips and blood samples were collected from 285 individuals for onchocerciasis diagnosis. Three tests were performed: the OV16 RDT (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Serum samples were obtained from two village matched case–control studies in the DRC to identify risk factors for epilepsy in onchocerciasis-endemic areas, one in Ituri [ 12 ] and one in Bas Uéle [ 13 ], a clinical trial assessing the effect of ivermectin on the frequency of seizures in O. volvulus -infected persons with epilepsy [ 14 ], controls with and without O. volvulus infection from a rapid epidemiological mapping of onchocerciasis (REMO) study in Ituri [ 15 ] and a diagnostic study among patients admitted to the Mosango general hospital, in Kwilu Province [ 16 ] ( Table 1 ). CSF samples of cases were obtained from persons with OAE from Maridi, an onchocerciasis-endemic region in South Sudan, and from persons without O. volvulus infection with acute-onset neurological conditions from the Mosango general hospital in Kwilu, DRC ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were obtained from two village matched case–control studies in the DRC to identify risk factors for epilepsy in onchocerciasis-endemic areas, one in Ituri [ 12 ] and one in Bas Uéle [ 13 ], a clinical trial assessing the effect of ivermectin on the frequency of seizures in O. volvulus -infected persons with epilepsy [ 14 ], controls with and without O. volvulus infection from a rapid epidemiological mapping of onchocerciasis (REMO) study in Ituri [ 15 ] and a diagnostic study among patients admitted to the Mosango general hospital, in Kwilu Province [ 16 ] ( Table 1 ). CSF samples of cases were obtained from persons with OAE from Maridi, an onchocerciasis-endemic region in South Sudan, and from persons without O. volvulus infection with acute-onset neurological conditions from the Mosango general hospital in Kwilu, DRC ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study among patients with neurological disorders enrolled at the Mosango hospital, a rural hospital located in an onchocerciasis hypo-endemic area of the DRC, revealed that 23.7% were OV16 ELISA test positive, with no other evidence of infectious etiologies including cysticercosis. As the OV16 ELISA test has a high specificity for the presence of O. volvulus antibodies [ 20 ], this means these individuals had been exposed to this infection. Moreover, the finding of three OV16-seropositive children under 10 years old suggests that there was relatively recent ongoing onchocerciasis transmission in the area where these children originated from (Mosango and Masimanimba).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that no other laboratory test or brain imaging investigations were done to identify the epilepsy etiology in our study participants. Moreover, the presence of O. volvulus antibodies was only assessed using an OV16 rapid diagnostic test, which is less sensitive compared to OV16 ELISA [ 31 ].…”
Section: Discussionmentioning
confidence: 99%